“Navigating growth challenges: A case study of radiation-induced growth retardation” - Ramya Selvam; Manjit Kour Mehta; Sivakumar N; Abhisek Bhattacharjee; Heena Agrawal; Shaleen Chandra (Oral Oncology Reports)
Growth hormone deficiency is a commonly observed pituitary hormone insufficiency in childhood cancer survivors who have undergone cranial radiation. It is the earliest and most prevalent deficiency, with an overall prevalence rate of 12.5 %. Patients who have received craniospinal radiation are at higher risk of experiencing short stature compared to those who have received only cranial radiation. The primary goal back then was achieving remission, and not minimizing adverse effects. However, with the current therapeutic modules, the adverse effects can be reduced significantly. Herein, we present a case of a 17-year-old who experienced growth retardation as a result of radiotherapy.